Global stability of discrete-time feedback nonlinear systems with descriptor positive linear parts and interval state matrices - Kaczorek, Tadeusz (1932- ); Ruszewski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The global stability of discrete-time nonlinear systems with descriptor positive linear parts, positive scalar feedbacks and interval state matrices is addressed. Sufficient conditions for the global stability of this class of nonlinear systems are established. The effectiveness of these conditions is illustrated using numerical examples.
Keywords: global stability; positive systems; nonlinear systems; discrete-time systems; feedback